2008
DOI: 10.1002/ejlt.200700189
|View full text |Cite
|
Sign up to set email alerts
|

Changes in sialylation of low‐density lipoprotein in coronary artery disease

Abstract: Reduction of LDL sialylation may correlate with coronary artery disease (CAD), but the details of this modification and its effect on CAD are not well studied. This study was aimed to show desialylation of LDL and to reveal more details of this modification. Blood samples were collected from 16 patients with CAD and 25 healthy individuals. Serum sialic acid was determined. LDL was extracted from all samples, and the interaction of the extracted materials with lectins (MAA, SNA, and DSA) was studied using the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Glycation reaction leads to alteration in the structure and function of biomolecules particularly proteins. AGE formation is known as a key element in diabetes complications [4146]. …”
Section: Resultsmentioning
confidence: 99%
“…Glycation reaction leads to alteration in the structure and function of biomolecules particularly proteins. AGE formation is known as a key element in diabetes complications [4146]. …”
Section: Resultsmentioning
confidence: 99%
“…265 A cohort study on 18 429 men and 19 414 women of age 59.5 ± 6.5 years along with 40 years of follow-up revealed that the elevated blood Sia concentration (>median 700 mg L −1 ) and pulse pressure (>median 70 mm Hg) could both independently predict the risk of cardiovascular incident for patients of cardiovascular diseases (P < 0.0001). 266 268 Furthermore, total Sia concentration in the serum and saliva of periodontitis patients increased in the comorbidity of cardiovascular diseases. 269 The total Sia concentration in the serum can also statistically identify (P < 0.0001) the induction of carotid atherosclerosis in humans caused by plaque deposition in the brain arteries.…”
Section: Sensors and Diagnostics Tutorial Reviewmentioning
confidence: 99%
“…267 The coronary artery disease also caused desialylation of low-density lipoprotein and increased the total Sia concentration in serum of the patients (mean 71.91 (68.33–75.60) mg dL −1 ; P < 0.001) compared to the healthy control (60.76 (57.04–65.92) mg dL −1 ). 268 Furthermore, total Sia concentration in the serum and saliva of periodontitis patients increased in the comorbidity of cardiovascular diseases. 269 The total Sia concentration in the serum can also statistically identify ( P < 0.0001) the induction of carotid atherosclerosis in humans caused by plaque deposition in the brain arteries.…”
Section: Biological Relevance Of Siamentioning
confidence: 99%